Genetic diversity assessment in Indian mustard (Brassica juncea L) for Alternaria blight tolerance using SSR markers (Journal of Oilseed Brassica, 2026)
Using SSR markers, genetic diversity in 20 Indian mustard [Brassica juncea (L.) Czern & Coss.] genotypes (14 advanced breeding lines, 4 tolerant germplasm accessions, 1 tolerant check, PAB 9511, and a susceptible check Varuna) was evaluated for Alternaria blight tolerance. Genotypes DRMR 2805 and DRMR 2806 found tolerant against Alternaria blight in the field conditions, gave the lowest AUDPC values of 10.0 and 8.25, and average lesion size of 4.5 mm and 4.2 mm, respectively. Genetic diversity evaluated among 20 Indian mustard genotypes using 25 Brassica species-derived-SSR markers, resulted into polymorphic amplicons producing a total of 88 alleles, ranging from 2 to 6 with an average number of 3.52 alleles/locus. The PIC values ranged from 0.1073 (MB5) to 0.8173 (BRMS-017) with an average of 0.3503. The UPGMA dendrogram divided all 20 genotypes into 2 main clusters. Genotypes DRMR 2805 and DRMR 2806 shared common cluster with PAB 9511, and were at par in their disease score indices to PAB 9511. The tolerant genotypes DRMR 2805 and DRMR 2806 identified in the present study can be used for introgression of Alternaria blight tolerance into the elite mustard cultivars in future breeding programmes